Reconstruction of Sea Ice Concentration in Northern Baffin Bay Using Deuterium Excess in a Coastal Ice Core From the Northwestern Greenland Ice Sheet. Issue 16 (18th August 2020) - Kurosaki, Yutaka; Matoba, Sumito; Iizuka, Yoshinori; Niwano, Masashi; Tanikawa, Tomonori; Ando, Takuto; Hori, Akira; Miyamoto, Atsushi; Fujita, Shuji; Aoki, Teruo
Abstract: Variations in the conditions of sea ice in the northern part of Baffin Bay and North Open Water polynya influence human activity in northwestern Greenland through oceanic circulation and heat balance between air and sea. To evaluate the impact of variations in sea ice conditions on the surrounding environment, it is important to understand the mechanism of sea ice variations over long periods. In this study, we estimated the age of the SIGMA‐A ice core collected northwestern Greenland Ice Sheet and researched the relationship between annual or seasonal deuterium excess (d‐excess) and seasonal sea ice concentration. We found that a temporal variation in the spring d‐excess in the ice core negatively correlated significantly with that of sea ice concentration in February–April in northern Baffin Bay from 1979–2005 ( r  = −0.61, p  < 0.001). Using this relationship, we reconstructed the temporal variations in sea ice concentrations for 100 years from the ice core drilled in the northwestern Greenland Ice Sheet. The sea ice concentration in the early twentieth century was lower than that in the present. The decrease in sea ice concentration was consistent with analytical results for marine sediments obtained from Baffin Bay. We also suggested that the sea ice concentration was controlled by atmospheric conditions from the 1920s to 1940s based on examinations of correlations with the North Atlantic Oscillation index and air temperature in Ilulissat and by oceanographic conditions from 1945–1955, 1959–1969, and 1982–1992 based on the Atlantic Multidecadal Oscillation index and meridional heat transport to western Greenland. Key Points: The moisture source for precipitation at the ice core drilling site on the northwestern Greenland Ice Sheet is the northern Baffin Bay Spring deuterium excesses in the ice core negatively correlated with sea ice concentrations in the northern Baffin Bay from 1979–2005 The reconstructed sea ice concentrations were low for the early twentieth century and varied with atmospheric and oceanographic factors